Prevalence and Characteristics of mcr-1-Producing Escherichia coli in Three Kinds of Poultry in Changsha, China - Hu, Jufang; Yang, Jie; Chen, Wenxin; Liu, Zhihong; Zhao, Qin; Yang, Hui; Sun, Zhiliang; Chen, Xiaojun; Li, Jiyun (Frontiers in Microbiology, 2022)
Colistin is one of the last-line drugs against difficult-to-treated multidrug-resistant Gram-negative bacteria. The emergence of mobile colistin resistance gene mcr-1 increased worldwide attention on colistin resistance. mcr-1 is the dominant gene that caused resistance to colistin in Chicken-derived Escherichia coli (E. coli) in China with a broad resistance spectrum and multiple drug resistance problems. Few studies on mcr-positive Escherichia coli (MCRPEC) from laying ducks and quails in China. Herein, the molecular and epidemiological characteristics of MCRPEC from three kinds of poultry farms (laying duck, quail and broiler) farms were investigated in Changsha, China. A total of 17 mcr-positive Escherichia coli (MCRPEC) strains were screened in 690 samples from three kinds of poultry farms. This is the first report of MCRPEC, to our best knowledge, derived from quail. All MCRPEC were resistant to colistin, sulfamethoxazole-trimethoprim, florfenicol, tetracycline and ciprofloxacin, and mild resistance to tigecycline, gentamicin, piperacillin/tazobactam, cefotaxime and ceftiofur. All strains were sensitive to meropenem and amikacin. By bioinformatics analysis, 17 MCRPEC, belonging to 11 MLST types, were distributed in phylogroup A (58.8%), phylogroup B1 (23.5%) and phylogroup D (17.6%). mcr-1were located in IncI2 plasmid with typical plasmid conjugation transfer part, type IV secretory system, and tellurium resistant protein, increasing the transmission capacity to other bacteria. The monitoring of colistin-resistant bacteria in poultry farms should be strengthened.